Synthesis, Characterisation and In Vitro Anticancer Activity of Catalytically Active Indole-Based Half-Sandwich Complexes - Joan J. Soldevila-Barreda; Kehinde B. Fawibe; Maria Azmanova; Laia Rafols; Anaïs Pitto-Barry; Uche B. Eke; Nicolas P. E. Barry (Molecules, 2020)
The synthesis, characterisation and evaluation of the in vitro cytotoxicity of four indole-based half-sandwich metal complexes towards two ovarian cancer cell lines (A2780 and A2780cisR) and one normal prostate cell line (PNT2) are presented herein. Although capable of inducing catalytic oxidation of NADH and able to reduce NAD+ with high turnover frequencies, in cells and in the presence of sodium formate, these complexes also strongly interact with biomolecules such as glutathione. This work highlights that efficient out-of-cells catalytic activity might lead to higher reactivity towards biomolecules, thus inhibiting the in-cells catalytic processes.